The Effect Of Providing Deep Breathing Relaxation Technique In Reducing Anxiety Levels In Section Caesarean Surgery Patients At RSIA Pasutri Bogor - Maryany, Syaffitry; Nurul Husnul Lail; Putri Azzahroh (International Journal of Midwifery and Health Sciences, 2024)
Background: In patients who will perform sectio caesarea surgery in general feel feelings of excessive anxiety due to worry in the process of surgery, and fear of the equipment used in the operating room. Objective: This study aims to determine and analyze the effect of deep breathing relaxation techniques in reducing the anxiety level of sectio caesarea surgery patients in the Operating Room of RSIA Pasutri Bogor. Method: This study used a quasy experimental research design with One Group pre test - post test. The population in the study was 55 mothers who performed sectio caesarea surgery in the operating room of RSIA Pasutri Bogor. The sample technique used in this study was purposive sampling. Results: From the results of the analysis in this study using the Wilcoxon signed test obtained p value = 0.000 (α < 0.05). Conclusion: So it can be concluded that there is a significant effect of providing deep breathing relaxation techniques in reducing the anxiety level of sectio caesarea surgery patients at RSIA Pasutri Bogor. Suggestion: Conduct more studies and the application of deep breathing relaxation techniques in reducing anxiety levels in cesarean section surgery patients.